Ureteroplasty Using Buccal Mucosa Graft in Complicated Long Segment Ureteral Stricture: Clinical Case Report - Sasnauskas, Gustas; Grybas, Aivaras (Lietuvos chirurgija, 2021)
Background. Recurrent proximal ureteral stricture is a complex rare disease that is difficult to treat. Post-operative scarring, impaired blood supply to the ureter, stricture-related stones, and chronic infection – all factors make the treatment even more complicated. Methods. There are various surgical procedures for ureteral reconstruction, however, most of them are very traumatic and quite often ineffective. Our case reports the first experience of treating a complicated recurrent proximal ureteral stricture with ureteroplasty using a buccal mucosa graft. Results. The patient had a 12-month post-operative follow-up. No stricture recurrence was observed and hydronephrosis decreased. Although the excretory function of the left kidney remained lower, serum creatinine became normal. The most important clinical outcome was the withdrawal of left flank pain. Conclusions. We are lacking high volume clinical trials for appropriate ureteral stricture treatment modality. All available publications in this field compare single cases or low volume studies. While buccal mucosa graft procedures are well established in urethral reconstruction, our case proves that buccal mucosa graft method can be successfully used for ureteroplasty as well, providing good post-operative functional outcomes.